Prescribed Fire Size, Patchiness, and Pyrodiversity in the Southeastern United States - Jennifer M. Fill; Raelene M. Crandall (EDIS)
This publication aims to provide information on how variation in prescribed fire size and heterogeneity and their impact over time relate to the habitat needs of animals and plants that live in frequently burned savannas. Written by Jennifer M. Fill and Raelene M. Crandall, and published by the UF/IFAS School of Forest, Fisheries, and Geomatics Sciences, August 2023.